Propuesta de manual de buenas prácticas de manufactura para la línea de yogur en la empresa “Camino a los Hieleros - Acan Ochog, Grimaneza Diocelina (2023)
The present research work had as main objectives, to carry out a diagnosis in the company "Camino a los Hieleros" and to develop a manual of good manufacturing practices for the yogurt line in order to improve and guarantee that the products are manufactured in conditions adequate sanitary conditions and the risks in their production and distribution are reduced. Taking into account that the BPM will be identified as a series of guidelines that will define the management and management of actions with the aim of ensuring favorable conditions for the production of safe food. All this was achieved with a mixed approach methodology, with a propositional level of a descriptive, bibliographical and field type, achieving the collection of information through investigative techniques such as the interview, the survey and the observation with their respective instruments, as was the case of the checklist that analyzed effective compliance with the national BPM technical regulations with resolution ARCSA-de-006-2017. Obtaining as a result one of the main shortcomings for non-compliance is the lack of documentation, since the criteria mention us in the verification of records. In turn, an average of 60% in compliance was identified; however, it was possible to determine that the organization did not have a manual of good manufacturing practices that integrates the activities that must be carried out. Therefore, an evaluation of the knowledge of these standards by the workers was also made in order to train them for the correct use and implementation of the BPM manual in the activities carried out. Thus concluding that the application of a theoretical framework that supports the design of a manual of good manufacturing practices is of great importance since it allows the employer to have the necessary resources to be put into practice, in turn the manual of good manufacturing practices. Delivered manufacturing becomes a fundamental tool in the development of productive activities complying with national regulations and without forgetting the hygienic safety that food products must have and satisfy the needs of customers.